Internal Control Systems and Financial Performance in an Indonesian Public Service Agency University: Evidence from Universitas BLU - OK Sofyan Hidayat; Situmeang, Chandra; Muhammad Ridha Habibi Z; Gultom, Endang Sulistyarini; Azhar Umar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines how internal control systems are linked to financial performance in an Indonesian public university operating under the Public Service Agency (Badan Layanan Umum, BLU) scheme. Using a descriptive-evaluative case study of Universitas BLU, the analysis draws on 2023 performance accountability records, SAKIP evaluation worksheets, internal audit documentation, budget realization evidence, and audited financial statements. To protect confidentiality, institutional identifiers were anonymized and nominal monetary amounts were proportionally masked, while ratios, scores, predicates, and analytical relationships were preserved. The university obtained a SAKIP score of 80.55 with an A predicate, improving from BB in the preceding year. Performance Measurement (77.00%) and Internal Performance Accountability Evaluation (78.00%) were the weakest control-related components. Gap analysis shows an 11.40-point difference between self-assessment and external assessment, with the largest correction in measurement-related controls. Financially, the anonymized budget ceiling of IDR 376,845,620,000 was realized at IDR 357,325,016,884, equivalent to 94.82% absorption and 5.18% efficiency, while the Budget Performance Value reached 90.49 against a target of 92. The audited financial statements received an unmodified opinion. The study concludes that internal control quality contributes to financial performance through planning discipline, hierarchical measurement, timely reporting, and systematic follow-up.